New insights on Polianthes montana (Asparagaceae, Agavoideae) and the description of P. aarodriguezii a new species, both from Sierra Madre Occidental, Mexico - Castro-Castro, Arturo; González-Bernal, Marco Antonio; Rojas-Aguilar, Edmi Itzel (Phytotaxa, 2023)
Botanical explorations in Sierra Madre Occidental, Mexico resulted in the location of new populations of Polianthes montana in the south of Durango state. This species is little known and there are conflicts on its identification and geographic distribution range, for these reasons here are provided discussions and an extended morphological description. Also, additional individuals from a Polianthes population were collected almost on the border of the states of Durango and Sinaloa, and after a rigorous analysis of the specimens, it was concluded that they do not belong to any of the known taxa in the genus and it is proposed here as a new species that morphologically resembles P. alboaustralis and P. montana but differs from the former in having (1–)3–4 ensiform leaves (vs. 2–6 linear), raceme inflorescence (vs. spike), perigone without a nectary (vs. nectary present in the floral tube), and filaments 6.5–9.7 mm long (vs. 2–10 mm long). From P. montana, it differs in the perigone size (5–5.5 × 0.4–0.7 cm vs. 2–2.8 × 0.3–0.5 cm), the orientation and size of perigone lobes (diffuse to divergent, 5.6–6.8 × 3.4–5 mm vs. adpressed to assurgent, 2.4–3 mm × 1.9–2.3 mm), longer filaments (6.5–9.7 mm vs. 5–5.4 cm), and styles (4.2–4.8 cm vs. 1.7–2 cm). Photographs, notes on phenology, geographic distribution, conservation status, and habitat are included, along with a map and an identification key to Polianthes subgenus Polianthes.